Cobweb Christmas - Climo, Shirley; Manning, Jane, 1960- (New York : HarperCollins, 2001)
Long ago in Germany, an old woman cleans her house and decorates her Christmas tree, hoping that this year she will witness some special Christmas Eve magic.
Keywords: Christmas -- Fiction; Christmas trees -- Fiction; Magic -- Fiction; Spider webs -- Fiction; Germany -- Fiction